Upaya Peningkatan Hasil Belajar Lari Jarak Pendek dengan Metode Bermain Burung dan Sangkar pada Siswa/I Kelas V SDN 3 Batu Layar Kecamatan Batu Layar Kabupaten Lombok Barat Tahun 2025 - Muhammad Janhari Rizky; M. Irham; Maulidin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to improve students’ learning outcomes in short-distance running through the implementation of the “Bird and Cage” play method among fifth-grade students at SDN 3 Batu Layar. The background of this research lies in the low achievement in short-distance running lessons, which is attributed to a lack of motivation, limited variation in teaching methods, and minimal student engagement during hysical education activities. This research employed a Classroom Action Research (CAR) design, conducted in two cycles following the Kemmis and McTaggart model, which includes planning, action, observation, and reflection phases. Theresearch subjects consisted of 14 students (6 boys and 8 girls). Data were collected using 60-meter sprint tests, observation sheets covering affective and psychomotor aspects, and documentation. The findings indicate a significant improvement in students' performance, with the percentage of students meeting learning mastery criteria increasing from 43% in the initial condition to 64% in the first cycle and 86% in the second cycle. Therefore, the “Bird and Cage” play method is proven to be effective in enhancing student participation and learning outcomes in short-distance running activities.